Performance of lactating dairy cows fed alfalfa haylage treated with bacterial inoculants at the time of ensilation - Michael V. Scheffel; R.K. Scoby; John E. Shirley (Kansas Agricultural Experiment Station Research Reports, 1996)
Sixty Holstein cows averaging 65 days in milk at the initiation of a 13-week study were used to evaluate three alfalfa haylages. Haylages were treated at the time of ensilation with either a Pioneer experimental inoculant (Treatment A), no inoculant (Treatment B), or Pioneer brand 1174® inoculant (Treatment C). Cows fed A had greater peak yields and tended to produce more milk than cows fed B and C. Milk fat percentages were 3.7, 3.66, and 3.59 for A, B, and C, respectively. Greater milk yield and butterfat percentage translated into higher (P<.05) daily fat production by cows fed A compared to C but not B.; Dairy Day, 1996, Kansas State University, Manhattan, KS, 1996;
Keywords: Dairy Day; 1996; Kansas Agricultural Experiment Station contribution; no. 97-115-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 771; Lactating cows; Alfalfa haylage; Inoculant